Factors affecting users' perception towards conservation of biodiversity in Matang Mangrove Forest Reserve (MMFR), Perak, Malaysia - Ramli, Fatin; Samdin, Zaiton; Abd. Ghani, Awang Noor; Mohamad Kasim, Mohamad Roslan (Universiti Malaysia Sarawak, 2018)
MMFR has been recognized as one of the best manages mangrove forest in the world. However, MMFR areas tend to be converted to other land uses such as industrial development, ecotourism areas, shrimp farming, aquaculture, housing area, and agriculture. Identifying the factors that affect the users’ perception towards biodiversity conservation may provide beneficial information to stakeholders including policy makers, users and MMFR authorities. This paper aims to explore the dimension of users’ perception towards conservation of biodiversity in MMFR. Face-to-face interviews were conducted among fishermen around MMFR and visitors to Matang Mangrove Eco-Education Centre. A factor structure comprised of ten factors within few perceptional dimension was derived. Method that has been used to explore the dimensions is the exploratory factor analysis (EFA). Findings revealed that the perception can be divided into two, among perceptional dimensions, sustainable ecosystem services appeared as the strongest perception followed by biodiversity of flora and fauna. The finding of this study is essential for MMFR management to formulate the appropriate and relevant policy for the MMFR authorities and users to attain long term benefits.